UNIVERSAL DESIGN FOR LEARNING IN COLLABORATIVE TEACHING: CHALLENGES AND POTENTIAL FOR SCHOOL INCLUSION (REMUNOM, 2026)
Considering the challenges faced by schools in effectively implementing school inclusion, especially in addressing the diversity present in classrooms, this study analyzes the implementation of Universal Design for Learning (UDL) articulated with collaborative teaching as a strategy to promote inclusive pedagogical practices. The objective is to understand the main challenges and potentialities of this articulation in the school context. To this end, a qualitative research approach is adopted, based on a literature review and theoretical analysis of studies addressing UDL, collaborative teaching, and inclusive education. Thus, it is observed that the main obstacles to the implementation of these practices are related to structural factors, such as the insufficiency of initial and continuing teacher education, workload overload, and the lack of time allocated for joint planning. On the other hand, the results indicate that the integration of UDL and collaborative teaching has significant transformative potential, as it enables the planning of accessible lessons from their conception and strengthens partnerships among teachers, fostering knowledge exchange and professional development. This allows the conclusion that overcoming these challenges requires a systemic transformation, including active commitment from school management and investments in teacher education policies and adequate working conditions, so that the principles of inclusive education can be effectively realized in everyday school practice.